2009
DOI: 10.1016/j.annepidem.2008.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight of Offspring, Maternal Pre-pregnancy Characteristics, and Mortality of Mothers: The Jerusalem Perinatal Study Cohort

Abstract: Purpose-To explore the association between birthweight in offspring, a marker of the intrauterine environment, and mortality in their mothers taking into account maternal pre-pregnancy characteristics, including maternal BMI, smoking, and socioeconomic status. Distinguishing the effects of offspring's birthweight and pre-pregnancy characteristics on maternal outcome may provide clues regarding mechanisms underlying the association between birth weight and maternal mortality.Methods-We studied long-term total m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 28 publications
6
24
1
Order By: Relevance
“…Verification from clinical records was not available. Nevertheless, the associations demonstrated in the present study between reported maternal attributes and measured cardio-metabolic traits more than 30 years later, as well as with long-term clinical outcomes in mothers described previously in this cohort 29 , together with the agreement with findings from studies in other populations (e.g. 5, 9, 16 ), lend support to the validity of the data.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Verification from clinical records was not available. Nevertheless, the associations demonstrated in the present study between reported maternal attributes and measured cardio-metabolic traits more than 30 years later, as well as with long-term clinical outcomes in mothers described previously in this cohort 29 , together with the agreement with findings from studies in other populations (e.g. 5, 9, 16 ), lend support to the validity of the data.…”
Section: Discussionsupporting
confidence: 90%
“…This finding can imply that birth weight does not measure the intrauterine environment well enough, although in our data birth weight appears to be associated to some extent with several of the cardio-metabolic outcomes examined (e.g. adiposity, BP, insulin, TG), as well as with clinical outcomes, such as mortality, demonstrated in previous studies in this cohort 29-31 . Alternatively, it could suggest that the associations of maternal adiposity (both mppBMI and GWG) and birth weight with offspring cardio-metabolic outcomes reflect different pathways linking early life events with adult health.…”
Section: Discussioncontrasting
confidence: 75%
“…Limitations of the study include: [1] The registries do not contain information on maternal comorbidities (infertility, obesity, diabetes mellitus, preeclampsia), and hence, it is difficult to evaluate bias since some pregnancy complications (e.g., preeclampsia) are considered protective for cancer but significant risk for death of cardiovascular causes [2]; parity was not evaluated as a cofactor due to lack of validated data: Our census database started in the early 1990s and some women included in the study might have given birth before this date [3]; we have no information on family history of cancer [4]; at the end of the follow-up period, only 1 % of women in study population and also in the group diagnosed with cancer were [55 years old, and thus at least for the hormonal-dependent cancers, conclusions should be restricted to women with pre-menopausal cancer [5]; we have no information on specific causes of death [6]; and the follow-up period was rather short; this may bias the results, since VLBW deliveries may be more common in the later years due to advances in fertility treatment and higher percentage of older primipara women, but the short follow-up precludes detecting primary outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are several strengths of this study: [1] availability of a population-based nation-wide health registry based on unique identity numbers affording valid and efficient study design with adequate follow-up [2]; the birth registry, cancer registry, and death reports completely include the entire population of Israel [3]; all cancer diagnoses are based on histology reports [4]; cancer sitespecific risk estimation [5]; all women may receive antenatal care, preventive medicine services, and ultimately hospitalization and cancer therapy gratis as mandated by the National Health Care Program, thereby minimizing influence of socioeconomic status on outcomes [6]; the criterion of a singleton VLBW is unequivocal and the limit of \1,500 g (\3rd percentile for term newborns) minimizes misclassification; and [7] all types of cancer were studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation